ANALISIS KONTRAKTUAL PERTANGGUNGJAWABAN PELAKU USAHA YANG WANPRESTASI BERBASIS ELEKTRONIK - NIM. A1011221247, JENNIFER OLIVIA (Jurnal Fatwa Hukum, 2026)
Abstract The development of electronic transactions through e-commerce platforms has created new legal consequences in contractual relationships between business actors and consumers, particularly when a breach of contract occurs. Disputes arising from electronic-based breaches of contract involve not only business actors and consumers but also the platform as the provider of the electronic system. The problem examined in this research is the legal consequences of breach of contract in electronic transactions as viewed from Article 1243 of the Indonesian Civil Code and Article 19 of Law Number 8 of 1999 concerning Consumer Protection based on the theory of contractual liability. This study aims to analyze the forms of business actors’ liability, consumers’ rights to remedies, and the limits of e-commerce platform responsibility in disputes concerning electronic-based breaches of contract from a theoretical perspective. This research employs a normative juridical method with a statutory approach. The legal materials consist of primary legal sources, including the Indonesian Civil Code, Law Number 8 of 1999 concerning Consumer Protection, Decision of the Medan District Court Number 183/Pdt.G/2018/PN Mdn, and the Terms and Conditions of the Tokopedia Platform. Secondary legal materials include legal literature, journals, and doctrines related to the theory of contractual liability. The collection of legal materials was conducted through library research and analyzed qualitatively to produce systematic and comprehensive conclusions. The results show that based on the theory of contractual liability, a breach of contract in electronic transactions gives rise to an obligation for business actors as debtors to compensate for damages as stipulated in Article 1243 of the Indonesian Civil Code and Article 19 of the Consumer Protection Law. Consumers as creditors have the right to demand performance, compensation, or cancellation of the agreement. Based on the principles of pacta sunt servanda and the principle of privity of contract, consumer losses arise directly from the breach committed by the business actor. Therefore, the primary legal responsibility remains with the business actor, while the Tokopedia e-commerce platform only bears limited responsibility as the provider of an electronic system that must be reliable and secure in accordance with its role and authority. Keywords: Breach of Contract, Contractual Liability, Electronic. Abstrak Perkembangan transaksi elektronik melalui platform e-commerce menimbulkan konsekuensi hukum baru dalam hubungan perikatan antara pelaku usaha dan konsumen, khususnya ketika terjadi wanprestasi. Sengketa wanprestasi berbasis elektronik tidak hanya melibatkan pelaku usaha dan konsumen, tetapi juga platform sebagai penyedia sistem elektronik. Permasalahan dalam penelitian ini adalah bagaimana akibat hukum wanprestasi dalam transaksi elektronik ditinjau dari Pasal 1243 Kitab Undang-Undang Hukum Perdata dan Pasal 19 Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen berdasarkan teori tanggung jawab kontraktual. Penelitian ini bertujuan untuk menganalisis bentuk pertanggungjawaban pelaku usaha, hak konsumen atas pemulihan, serta batas tanggung jawab platform e-commerce dalam sengketa wanprestasi berbasis elektronik secara teoritis. Metode penelitian yang digunakan adalah penelitian yuridis normatif dengan pendekatan perundang-undangan (statute approach). Bahan hukum yang digunakan meliputi bahan hukum primer berupa Kitab Undang-Undang Hukum Perdata, Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen, Putusan Pengadilan Negeri Medan Nomor 183/Pdt.G/2018/PN Mdn, serta Syarat dan Ketentuan Platform Tokopedia. Bahan hukum sekunder berupa literatur, jurnal, dan doktrin hukum terkait teori tanggung jawab kontraktual. Pengumpulan bahan hukum dilakukan melalui studi kepustakaan dan dianalisis secara kualitatif untuk menghasilkan kesimpulan yang sistematis dan komprehensif. Hasil penelitian menunjukkan bahwa berdasarkan teori tanggung jawab kontraktual, wanprestasi dalam transaksi elektronik menimbulkan kewajiban ganti rugi bagi pelaku usaha sebagai debitur sebagaimana diatur dalam Pasal 1243 KUHPerdata dan Pasal 19 UUPK. Konsumen sebagai kreditur berhak menuntut pemenuhan prestasi, ganti rugi, atau pembatalan perjanjian. Berdasarkan asas pacta sunt servanda dan asas personalitas perjanjian, kerugian konsumen merupakan akibat langsung dari wanprestasi pelaku usaha sehingga tanggung jawab utama berada pada pelaku usaha. Platform e-commerce Tokopedia hanya berperan sebagai penyedia sistem elektronik sehingga tanggung jawabnya terbatas pada penyelenggaraan sistem yang andal dan aman sesuai dengan fungsi dan kewenangannya. Kata Kunci: Wanprestasi, Tanggung Jawab Kontraktual, Elektronik.